Management Uncertainty and Audit Fees - Vali Khodadadi (Shahid Bahonar University of Kerman, 2017)
The purpose of this study is to investigate the relationship between management uncertainty and audit fees in the companies listed in the Tehran Stock Exchange, TSE. Four hypotheses were developed and data from 81 companies in the TSE in the period 2006 to 2014 were analyzed, using a regression panel data model with fixed effects. The findings indicated that there exists a significant positive relationship between management uncertainty and audit fees. Also, the size of audit firm and auditor tenure have significant positive effects on the relationship between management uncertainty and audit fees. In addition, the findings showed that in the cases of loss in a company before changing CEO, the positive relationship between management uncertainty and audit fee is prominent. In general, the findings confirm the claim that auditors increase audit efforts (reflected in audit fees) to determine the risk associated with management uncertainty.